Luther on faith and love : Christ and the law in the 1535 Galatians commentary - Kim, Sun Young (Emerging scholars., 2014)
There has been a distinct tendency in modern scholarship to underestimate Luther's teaching on love by overemphasizing his teaching on justification. Calling this tendency into question, this volume advances the thesis that Luther's teaching on faith and love operates as the overriding thematic pair in the dynamics of Christ and the law-structurally and conceptually undergirding the 1535 Galatians commentary. The research situates itself in the landscape of Luther scholarship via a special attention to Finnish Luther scholars and scholarship.